Cancer genomics and bioinformatics in Latin American countries: applications, challenges, and perspectives - Torres-Narvaez, Erika Sofia; Mendivelso-González, Daniel Felipe; Artunduaga-Alvarado, Juan Andrés; Ortega-Recalde, Oscar (Frontiers in Oncology, 2025)
Next-generation sequencing (NGS) technologies have revolutionized research and precision medicine in patients with cancer. Progress in this area has been accompanied by the development of efficient and robust bioinformatics methods along with computational resources able to handle the growing amount and complexity of sequencing data. Importantly, the implementation of such approaches has not been uniform around the globe and several regions, including Latin American countries, remain lagging behind in cancer genomics and precision oncology. Likewise, numerous studies have highlighted the complexity and particularities of such populations in terms of genetic background, healthcare systems and human and technological resources. In this review, we aim to describe current clinical applications of NGS-based tests, focusing on their bioinformatics analyses and implementation in Latin America. Furthermore, we describe several opportunities for development, perspectives, and challenges that face genomic data analysis in this geographical area. We expect this review to provide an up-to-date overview of cancer genomics and bioinformatics in Latin America, serving as a valuable resource for both local and international cancer researchers.